Lost and found: the Benmore and other Clydeside fernery buildings constructed by James Boyd & Sons of Paisley - David Gray (Sibbaldia)
Digital library searches undertaken by the author have recently uncovered a small but significant archive of information about the Benmore fernery, linking it to glasshouses and other contemporaneous fernery buildings in Scotland. It is now possible to verify the date of the original building to the early 1870s. Wider context and background details are provided by briefly exploring horticultural trends and architectural innovations from this period. Thereafter, the known Clydeside fernery buildings constructed by James Boyd & Sons are reconsidered, providing insight into unknown and previously missing details of the Benmore version. In 2009, from a ruinous condition, the Benmore fernery was the subject of a significant restoration led by a Glasgow-based team of conservation-accredited architects. Aspects of this practical work are summarised. The article concludes by exploring the wider topics of garden history and conservation and highlights the role of botanic gardens in promoting the sometimes overlooked value of garden heritage.